Geomorphic expressions of active rifting reflect the role of structural inheritance: a new model for the evolution of the Shanxi Rift, northern China - M. Froemchen; K. J. W. McCaffrey; M. B. Allen; J. van Hunen; T. B. Phillips; Y. Xu (Solid Earth, 2024)
Many rifts are influenced by pre-existing structures and heterogeneities during their evolution, a process known as structural inheritance. During rift evolution, these heterogeneities may aid rift nucleation, rift growth, and the segmentation of faults; encourage the linkage of various segments; or even inhibit the formation of faults. Understanding how structural inheritance influences early rift evolution could be vital for evaluating seismic risk in tectonically active areas. The Shanxi Rift in the north of China is an active rift system believed to have formed along the trend of the Proterozoic Trans-North China Orogen; however, the influence of these pre-existing structures on the present-day rift architecture is poorly understood. Here, we use tectonic geomorphological techniques, e.g. the hypsometric integral (HI), channel steepness (ksn), and local relief, to study the evolution of the Shanxi Rift and identify areas of higher tectonic activity. We found that the HI was less sensitive to lithology and more valuable in evaluating the tectonic signal and that activity is concentrated in two rift interaction zones (RIZs) formed between the Xinding, Taiyuan, and Linfen basins. We then evaluated the relationship between the active faults and mapped pre-existing structures, finding that many faults formed parallel to inherited structures, while faults in the RIZs often cross-cut these structures. Based on these observations, we propose a new model for the evolution of the Shanxi Rift, where inherited structures play an important role in the initial segmentation of the rift, which, in turn, controls the development of the RIZ structures.